Determination of Cyanide in Concrete Roofing Tiles by Differential Pulse Voltammetric Method - Jaroon Junsomboon (Science Faculty of Chiang Mai University, 2019)
Differential pulse cathodic voltammetric technique with a hanging mercury drop electrode (HMDE) has been developed for the determination of cyanide in a water extract of concrete roofing tile samples. The sample was extracted with water for 24 h according to the TIS 535-2556 standard method. An aliquot of 5 mL of the extracted solution and 5 mL of electrolyte solution (0.2 M KOH + 0.2 M H3BO3) were put in a voltammetric cell, stirred at 2000 rpm, and purged with nitrogen gas for 3 min. Then, a constant potential of 0.00 V versus Ag/AgCl reference electrode was applied to the working electrode for 10 s; the differential pulse waveform was cathodically scanned from 0.0 to - 0.45 V for recording a voltammogram. Reduction peak current at peak potential of - 0.22 V vs Ag/AgCl electrode was proportional to cyanide concentration. Relative standard deviation for 11 replicate determinations of 0.04 mg L-1 CN- was 2.62%. Percentage recovery obtained by spiking 0.04 mg L-1 CN- to the sample solution was found to be 95%, and a detection limit of 0.001 mg L-1 was achieved. The developed method provides good sensitivity and selectivity, which is suitable for quality control of cyanide in the concrete roofing tile products, and it is simple, convenient operation, and low reagent consumption.